PENGEMBANGAN MEDIA PEMBELAJARAN TEKA TEKI EDUKATIF PADA MATERI BARISAN ARITMATIKA DAN GEOMETRI DI SMA BAITUL RAHMAN SEI MENCIRIM - Dela Puspita, Anggun; Balqis, Annisa; Wandini, Rora Rizki (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2023)
Geometry is one of the important roles in mathematiecs that student need to learn, because it can helpdevolop skills in problem solving. However, there are still errors that often occur in solving problems regarding geometry. This research aims to produce learning media based on a cooperative approach as a tool for learning arithmetic and geometric sequences to find out whether this educational smart puzzle learning media can be effectively applied in learning arithmetic and geometric sequences. The development model used is the 4D model proposed by Thigarajan which consists of four stages, namely the definition, design, development and deployment stages. The results of this effectiveness test show that student learning achievement by learning using educational smart puzzle media is better than learning without using this media. So it is concluded that this educational smart puzzle learning media is effective and feasible to apply in learning arithmetic and geometric sequences is SMA Baitul Rahman Sei Mencirim.